A close look at current γδ T-cell immunotherapy - Ma, Ling; Feng, Yanmin; Zhou, Zishan (Frontiers in Immunology, 2023)
Owing to their antitumor and major histocompatibility complex (MHC)-independent capacities, γδ T cells have gained popularity in adoptive T-cell immunotherapy in recent years. However, many unknowns still exist regarding γδ T cells, and few clinical data have been collected. Therefore, this review aims to describe all the main features of the applications of γδ T cells and provide a systematic view of current γδ T-cell immunotherapy. Specifically, this review will focus on how γδ T cells performed in treating cancers in clinics, on the γδ T-cell clinical trials that have been conducted to date, and the role of γδ T cells in the pharmaceutical industry.